2006
DOI: 10.1080/03004430500232680
|View full text |Cite
|
Sign up to set email alerts
|

Parent–child interaction and children’s number learning

Abstract: Two groups of Chinese four-year-olds and their parents' interaction in joint activities were analyzed and compared. The children in Group 1 were high scorers in written number skills and the children in Group 2 were low scorers. Eighty-five dyads participated in four separate 15-minute joint activities such as book reading, mathematical worksheets, blank paper and blocks. A mini-questionnaire was also administered. The results indicated that a wide variety of mathematics and interactive strategies were involve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
46
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 10 publications
3
46
0
Order By: Relevance
“…Huntsinger, Jose, Larson, Krieg, & Shaligram, 2000;Zhou et al, 2006), and a comprehensive ecological observation of preschool environments (i.e. Ecobehavioral System for the Complex Assessment of Preschool Environments; Greenwood, Carta, Kamps, & Delquadri, 1997).…”
Section: Parent-child Math Interaction Codingmentioning
confidence: 99%
“…Huntsinger, Jose, Larson, Krieg, & Shaligram, 2000;Zhou et al, 2006), and a comprehensive ecological observation of preschool environments (i.e. Ecobehavioral System for the Complex Assessment of Preschool Environments; Greenwood, Carta, Kamps, & Delquadri, 1997).…”
Section: Parent-child Math Interaction Codingmentioning
confidence: 99%
“…According to the preschool and kindergarten education guideline for the city of Beijing, 3-and 4-year-old children would be taught how to count up to five objects and understand the quantities up to five objects (magnitude comparison). Second, Chinese parents give informal direct mathematics instruction and encourage mathematicsrelated activities such as counting fingers, stairs, and family members; solving arithmetic problems; and determining set sizes (Zhou et al, 2006(Zhou et al, , 2007. These activities about numbers would convey redundant kinesthetic, visual auditory, and temporal information about numerical magnitudes (Siegler & Mu, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Related to home experiences, studies have shown that parental attitude and practices also vary greatly where East Asian parents show high expectations for their children's mathematics education and provide more support and encouragement when compared to U.S. parents (e.g. Zhou et al 2006). Further, East Asian teachers have been found to possess in-depth knowledge of mathematics and provide multiple strategies and modes for solving a single problem (e.g.…”
mentioning
confidence: 94%
“…Researchers claim parental involvement and practices as one of the major contributing factors for young East Asian children's advanced math skills prior to formal school entry (Zhou et al 2006). Because almost all children rarely experience direct instructions on mathematics in preschool or other childcare settings, much of their early number knowledge is communicated through a wide range of mathematical relevant interactions embedded in their everyday activities with their parents.…”
mentioning
confidence: 99%